Condicionamientos estructurales y desistimiento criminal de penados al término de la libertad condicional en Paraguay (2021)
Studies on criminal desistance associate the rupture with crime to various personal and social factors, as well as to the agency and perception of personal self-efficacy of. Despite increasing criminological interest in the topic of criminal career cessation, theoretical inconsistencies, imprecise definitions, and the rules used to measure it, continue to hinder a comprehensive understanding. This article analyzes the role of structural conditioning factors, such as family, education, and previous work experience, in criminal desistance, using an interpretive approach and qualitative techniques including: analysis of court files ans interviews with four female enforcement judges, two public defenders, and particularly, the accounts of 15 former convicts of various criminal categories, who successfully completed their probation period. These are adult men who served sentences in two Paraguayan prisons characterized by overcrowding, violence, lack of access to fundamental rights and the absence of prison treatment programs, and who voluntarily agreed to collaborate with the research. The findings show that resources and prosocial skills before imprisonment and their ability to maintain or increase them during imprisonment and in liberty are essential for them to stay away from crime, despite their time in the penitentiary system.